1995
DOI: 10.1021/ma00125a017
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Effects on the Disordered Phase of Block Copolymer Melts

Abstract: We have measured the effect of high pressure on the scattering from the disordered state of a styrene-isoprene diblock copolymer containing 48 wt % styrene (Mw ~16 500). Small-angle X-ray scattering measurements performed at the Cornell High Energy Synchrotron Source (CHESS) show an increase in the aspect ratio of the scattering maximum and a decrease in the angle at which the maximum occurs with increasing pressure. Within the context of the mean-field theory of block copolymer phase behavior originally devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
52
1
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 13 publications
4
52
1
1
Order By: Relevance
“…[17][18][19][20] Some researchers have used the RPA-based equations to analyze pressure-dependent scattering data from type I experiments on blends and block copolymers. In all cases, 1,3,4,[6][7][8]10,11 the data from homogeneous, one-phase systems are consistent with the RPA if and the statistical segment lengths are assumed to be pressure dependent. This is in addition to the usual temperature dependence of these parameters.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…[17][18][19][20] Some researchers have used the RPA-based equations to analyze pressure-dependent scattering data from type I experiments on blends and block copolymers. In all cases, 1,3,4,[6][7][8]10,11 the data from homogeneous, one-phase systems are consistent with the RPA if and the statistical segment lengths are assumed to be pressure dependent. This is in addition to the usual temperature dependence of these parameters.…”
Section: Introductionmentioning
confidence: 60%
“…[21][22][23] Other groups have questioned the applicability of the RPA to type I experiments because of the incompressibility assumption, and different modifications of the original RPA have been proposed. 1,4,8 The data obtained in type II experiments are invariably analyzed by using the Clausius-Clayperon equation, 24 where ∆V p and ∆H p are the volume and enthalpy changes associated with the phase transition.…”
Section: Introductionmentioning
confidence: 99%
“…Note that the FH theory, being incompressible, would suggest that pressure is an irrelevant variable. In contrast to FH theory, as showed above, the experimental results proved that pressure can play an important role in the phase separation of polymer containing systems (Hajduk et al, 1995(Hajduk et al, , 1996Jiang et al 2002). The behavior of ternary polymer mixtures containing a diblock copolymer with homopolymer and toluene as a function of mixture composition and temperature were investigated to obtain experimental phase diagram for solvent/copolymer/ homopolymer mixture.…”
Section: Abnormal Pressure Dependence Of the Phase Boundaries In Tl/ mentioning
confidence: 83%
“…However, an attempt to predict this rate based on measured structural parameters yielded an underestimation by a factor or two. 10 Hammouda et al 11 also found an increase in ODT at rate of approximately 0.2°C/MPa in a concentrated polystyrene-polyisoprene in the nonpreferential solvent dioctyl phthalate (DOP). Additionally, they observed a pressure induced increase in scattering at low q, defined as q ) (4π/λ) sin(θ/2) where θ is the scattering angle and λ is the wavelength of the incident radiation.…”
Section: Introductionmentioning
confidence: 97%